2014
DOI: 10.1186/s13028-014-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and phenotypic characteristics of myocarditis in two pigs infected by foot-and mouth disease virus strains of serotypes O or A

Abstract: Myocarditis is often cited as the cause of fatalities associated with foot-and-mouth disease virus (FMDV) infection. However, the pathogenesis of FMDV-associated myocarditis has not been described in detail. The current report describes substantial quantities of FMDV in association with a marked mononuclear inflammatory reaction, interstitial edema and cardiomyocyte degeneration in the myocardium of two pigs that died during acute infection with either of two different strains of FMDV. Despite similar clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
(20 reference statements)
1
15
0
Order By: Relevance
“…Examination of FMDV-RNA-positive hearts from infected fetuses indicated that infection was associated with mild to moderate degeneration and necrosis of the cardiomyocytes consistent with earlier findings in sheep, goats, pigs, and adult cattle infected with FMDV [4, 34, 53, 54]. Additionally, affected hearts had variable, moderate infiltration of inflammatory cells, predominantly lymphocytes dissecting myofibers consistent with findings previously described in sheep [10], pigs [53] and cattle [55]. In previous works, FMDV-infected lambs had lymphocytic myocarditis which was considered as a significant stimulus of the cardiac myocytes to release inducible nitric oxide synthase enzyme (INOS) and thereby increase production of nitric oxide (NO) [56, 57].…”
Section: Discussionsupporting
confidence: 87%
“…Examination of FMDV-RNA-positive hearts from infected fetuses indicated that infection was associated with mild to moderate degeneration and necrosis of the cardiomyocytes consistent with earlier findings in sheep, goats, pigs, and adult cattle infected with FMDV [4, 34, 53, 54]. Additionally, affected hearts had variable, moderate infiltration of inflammatory cells, predominantly lymphocytes dissecting myofibers consistent with findings previously described in sheep [10], pigs [53] and cattle [55]. In previous works, FMDV-infected lambs had lymphocytic myocarditis which was considered as a significant stimulus of the cardiac myocytes to release inducible nitric oxide synthase enzyme (INOS) and thereby increase production of nitric oxide (NO) [56, 57].…”
Section: Discussionsupporting
confidence: 87%
“…Myocarditis typically occurs in young animals and is associated with specific viral strains and poorly understood host-specific factors (Arzt et al 2011a). The higher fatality in the Hill zone may have been associated with that region's higher quantities of pigs which have been demonstrated to be highly susceptible to myocarditis from certain strains of FMDV (Stenfeldt et al 2014). Additional factors which might have contributed to differential fatality include climatic influences, environmental stability of secondary pathogens or opportunistic organisms, and access to adequate quality and quantity of feed and water.…”
Section: Discussionmentioning
confidence: 99%
“…FMD-related deaths are often attributed to acute viral myocarditis, even in cases when the precise cause of death has not been definitively determined. However, it is well established that acute FMDV infection may cause infection of the myocardium, leading to heart failure and sudden death ( 56 58 ). The gross pathological findings associated with FMDV-induced myocarditis may range from complete absence of visible lesions to distinct areas of pallor on the cardiac surface that extend into subjacent myocardium (Figure 4 A).…”
Section: Fmd In Pigsmentioning
confidence: 99%
“…Generally, necrosis and inflammation coexist in every lesion with continuum of severity. Inflammation typically includes lymphohistiocytic infiltration and edema, whereas cardiomyocyte degeneration and necrosis may occur as individual cells, small clusters, or may be regionally extensive (Figure 4 C) ( 58 ). Regions of architectural disruption may have evidence of viral replication including presence of viral antigens and nucleic acids detectable by immunomicroscopy and in situ hybridization, respectively (Figure 4 D).…”
Section: Fmd In Pigsmentioning
confidence: 99%
See 1 more Smart Citation